Transforming Transient Drain Spacing Formula to Predict Water Table Fluctuation in Response to Constant Recharge - Verma, Chhedi Lal; Singh, C.S. (Journal of Soil Salinity and Water Quality, 2023)
A method was developed for transforming transient drain spacing equations for predicting water table heights in response to constant rainfall without ignoring flow above drain level between parallel subsurface drains. The Integrated Hooghoudt drain spacing equation was transformed for predicting rise and fall of water table heights in response to constant recharge. The equation was tested in subsurface drained fields with drain spacing of 50 m and 75 m and compared with existing drain equations. Average per cent deviations of predicted water table heights by Integrated Hooghoudt equation with instantaneous rise, Integrated Hooghoudt with rise factor, van de Leur Maasland, van Schilfgaarde and de Zeeuw Hellinga equations were 25.72, 16.71, 27.38, 27.20 and 24.50% with corresponding RMSD of 0.2083, 0.2110, 0.1663, 0.2020 and 0.1769, respectively for 50 m drain spacing plot and 15.90, 22.56, -28.54, -14.57 and 14.39% with corresponding RMSD of 0.1779, 0.2070, 0.2187, 0.1226 and 0.0911, respectively for 75 m drain spacing plot. The approach for transforming a transient drain spacing equation to water table predicting equation in response to constant recharge is validated.